New grafts for anterior cruciate ligament grafting using the «all-inside» method - Golovakha, Maksim; Orljanski, Weniamin; Benedetto, Karl (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2019)
Improving the technique of anterior cruciate ligament (ACL) reconstruction is developing in the following areas: reduction of surgical trauma, improvement of the anatomical position of the graft, increased strength of its attachment, stimulation of regeneration of attachment sites, modification of postoperative of rehabilitation treatment. The «all-inside» technique meets most requirements. The recovery period of the patient after ACL reconstruction significantly associated with the speed of integration of the transplant into the surrounding tissue. Objective: to develop a method for using transplants from the patellar ligament (BTB) and quadriceps tendon (QT) during ACL reconstruction according to the «all-inside» technique. Methods: the study included patients (12 men, 2 women) who in addition to ACL reconstruction had meniscus removal, meniscus suture, cartilage shaving and microfracturing of small defects (no more than 3 cm2 ). Revision operations was carried out in 3 patients. The channels were drilled with a RetroDrill® tool or FlipCutter®. The grafts in the femur and tibia were fixed using TightRope® suspension system or its analogue. Results: a method was developed for the use of BTB and QT grafts with 180° turnover of bone fragment to restore ACL according to the method «allinside». Clinical testing of the method in primary and the revision of the ACL reconstruction has shown good and excellent results. On 2–3 days, VAS pain indicator is 3–4 points, after a week all patients recovered knee flexion up to 90°. Instability of the knee joint is not detected. After 12 months 71.2 % of patients were assigned to group A on the IKDC scale. Conclusions: proposed method can be used in the primary and, especially, revision ACL reconstruction, because by turning the bone fragment you can get the end of the graft significantly larger diameter comparing with traditional methods for the preparation of BTB and QT transplants.